Potensi Dan Tantangan Dalam Usaha UMKM Rotan Di Gunung Mas - Tamara, Depi; Rahayu, Sapna; Nasrida, Muhammad Farras; Benius, Benius (STAI Denpasar Bali, 2023)
The rattan MSME business has long been part of the handicraft industry in Gunung Mas. However, this business is still faced with various challenges such as intense competition, limited raw materials, and a lack of understanding of the market. This study aims to evaluate the potential and challenges in the MSME rattan business in Gunung Mas. The research was conducted through interviews with several rattan MSME business owners and secondary data analysis. The results of the study show that the business potential of rattan SMEs in Gunung Mas is still quite large, especially because rattan is a raw material that is easy to obtain in Gunung Mas and has high aesthetic value. However, this business is faced with very tight competition from cheaper imported rattan products. In addition, the lack of understanding of markets and modern technology is a challenge that must be faced by MSME rattan business owners in Gunung Mas. Based on the results of this study, rattan MSME business owners need to improve their understanding of modern markets and technology and develop more effective marketing strategies. In addition, the government and the community need to provide support and appreciation for local rattan products as an effort to increase the competitiveness and sustainability of rattan MSME businesses in Gunung Mas.